The Challenge of Assessing Mild Neuroinflammation in Severe Mental Disorders - Bechter, Karl (Frontiers in Psychiatry, 2020)
The field of psycho-neuro-immunology provides recently new insights into the etiology and pathogenesis of severe mental disorders (SMDs). The mild encephalitis (ME) hypothesis years ago proposed a subgroup of patients to prevail in SMD cohorts, but ME remained undetected with available diagnostic methods, however low-grade neuroinflammation causally underlying respective actual psychopathology during disease course, was preferentially expected in SMDs of the broad schizophrenic and affective spectrum. Recently in neurology an emerging subgroup of cases of Autoimmune Encephalitis was described, which includes limbic encephalitis, suffering from various neurological syndromes. Only now another subgroup with predominant or pure psychiatric symptomatology was described with consensus criteria of Autoimmune Psychosis in SMD cohort. Herein a major clinical challenge is to identify mild neuroinflammation in vivo in the individual case. The background of these recent developments and the many remaining challenges for research and clinical diagnosis of mild neuroinflammation are reviewed and discussed.